Instagram as a Tool of Diffusion for the Livestock Industry - Savannah Locke; Karen Hiltbrand; Katie Corbitt; Darcey Richburg; David Shannon; Soren P. Rodning; Jason T. Sawyer; Don Mulvaney (Journal of Applied Communications, 2023)
Studies have shown that more people are getting their information through social media (SM). With so much misinformation presented in global media, it is difficult for consumers to distinguish what is true and what isn’t. With negative images and minimal context, consumers have a tendency to believe and trust what they see on SM. After IRB approval, a survey study was launched on Qualtrics and accessed via email. Using Instagram as platform, this study presented 5 cognitively and 5 emotionally oriented posts focused on the aspects of animal welfare, diet/health, and environment/sustainability. Prior to viewing the Instagram posts, study participants were given a 5-scale Likert pre survey assessing their opinions about their views of animal welfare, diet/health of consumers of red meat and environment/sustainability for the beef industry. Participants subsequently viewed the posts and then took a post survey. SPSS was used to analyze responses with t-tests and frequencies. ATLAS was used to code for negative and positive key words in open responses. Results showed that participant’s views about the beef industry improved (p < .05) after viewing the media posts for welfare and that participants favored the suggestions that beef cattle are treated humanely. Participants were unsure of the effects that beef consumption has on consumers’ diet and health as well as the environment. Qualitative results suggest that viewing of the posts had a favorable impact on consumer’s opinions.
Keywords: Animal Welfare; Beef; Diet/Health; Environment/Sustainability; Social Media